(untitled) (Journal of Social Sciences Review, 2025)
The current study investigates the different causes of truancy at secondary school level in the Pakistan context. For this purpose, public and private sector secondary school teachers were selected. The population of the study were 1316 Public and Private secondary school teachers of District Attock. A total of 420 secondary school teachers from public sector (220) and private sector (200) were selected as the sample of the study. A stratified random sampling technique was used to collect data. The study was descriptive. A self-developed questionnaire based on five-point Likert’s scale was used to seek the responses of the respondents. The scale was highly reliable. The study used an independent sample t.test to ascertain difference based on sectors and gender. The results reveal that teacher related causes were the most influential causes contributing to truancy. Other causes that related to family, school environment and peers were also found contributory to truancy of students. Based on findings it was recommended that teachers should be morally and emotionally trained. School environment should be attractive. Parents should be cooperative.